PEMBERDAYAAN DESA MELALUI PELATIHAN PENGOPERASIAN MICROSOFT EXCEL DALAM ADMINISTRASI DATA MATEMATIS DESA - Andari, Tri; Lusiana, Restu (Jurnal Terapan Abdimas, 2016)
The purpose of this training is that trainees are able to master the operation of Microsoft Excel for data processing mathematical administration in the village. Operation of Microsoft Excel training activities carried out in two village in the district Panekan partners namely in the village and the village Milangasri Wates. Training activities conducted using survey methods, lectures, practical training and consultation discussions. In this community service activities we undertake the operation of Microsoft Excel training for administrative data processing mathematically in the village. To know the indicators of achievement of the control operation of Microsoft Excel training participants we conducted a series of evaluations at each stage of activity. From the results of the evaluation carried out, showing that the operation of Microsoft Excel training is effective, it can be seen from the enthusiasm of the participants in the training. Given that most of the data processing mathematical administration in the village do with Microsoft Excel so by mastering how to operate the program, the data can be documented village easier, faster, and more complete. It is an indicator of the importance of improving the quality of village administration services and related processes performed by the village. The enthusiasm and activeness of the participants showed that this training is required by the Village.Keywords: Empowerment, Training, Microsoft Excel, Data Administration Mathematical